Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3856/vol42-issue1-fulltext-9
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and reproductive aspects of puffer fish Sphoeroides annulatus (Jenyns, 1842) (Osteichthyes: Tetraodontidae), landed in Teacapan, Sinaloa, Mexico

Abstract: ABSTRACT. The puffer fish Sphoeroides annulatus is an important target species for the artisanal fishing fleets of NW Mexico. To obtain information on population structure of the local stock, we determined the total length and total weight (TL and TW) ranges, sex ratio and reproductive stages of 745 specimens of this species, landed from May 2010 to April 2011 in Teacapán, Sinaloa, NW Mexico. TL ranged from 15 to 40 cm and TW from 100 to 1600 g. There were no differences between mean TL (27.41 ± 4.14 cm) and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…The size at first sexual maturity is defined as the length at which a randomly chosen sample has a 50% chance of being mature (Somerton, 1980). Earlier, the logistic curve for estimating the size at first sexual maturity has been successfully used for several species of fishes (Bandpei et al, 2011;Valdez-Pineda et al, 2014;Nandikeswari, 2016;Freitas et al, 2016;Peixoto et al, 2018). The logistic model for estimating the size at first sexual maturity by visual inspection of gonads (L 50 Maturity scale) revealed that female individuals of N. hexagonolepis attained the first sexual maturity at TL 32.9 cm.…”
Section: Discussionmentioning
confidence: 99%
“…The size at first sexual maturity is defined as the length at which a randomly chosen sample has a 50% chance of being mature (Somerton, 1980). Earlier, the logistic curve for estimating the size at first sexual maturity has been successfully used for several species of fishes (Bandpei et al, 2011;Valdez-Pineda et al, 2014;Nandikeswari, 2016;Freitas et al, 2016;Peixoto et al, 2018). The logistic model for estimating the size at first sexual maturity by visual inspection of gonads (L 50 Maturity scale) revealed that female individuals of N. hexagonolepis attained the first sexual maturity at TL 32.9 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on reproductive biology are essential to understand fish population dynamics (Brown‐Peterson et al ., ). Marine pufferfishes have a range of annual reproductive cycles, from seasonal, with one or two actively reproductive periods to year‐round gamete production (Sánchez‐Cárdenas et al ., ; Valdez‐Pineda et al ., ). However, information the reproductive biology of E. guttifer has not previously been reported.…”
Section: Measurement and Meristic Collected From A Specimen Of Ephippmentioning
confidence: 97%
“…Valdez‐Pineda et al. (2014) studied the population structure and reproductive aspects of the local stocks of puffer fish, Sphoeroides annulatus (Jenyns, 1842) (Osteichthyes: Tetraodontidae), in Mexico using morphometric characters. It is known that ecological and genetic factors influence development and maturation of individual fish species leading to distinguishable stock characteristics which can be perceived through morphometric analyses (Cadrin, 2000).…”
Section: Introductionmentioning
confidence: 99%